Efficacy of anti-poverty and welfare programs in Portugal : the joint impact of the CSI and RSI - Rodrigues, Carlos Farinha (2010)
The aim of this paper is to estimate the joint impact on the distribution of household income and poverty of the implementation of two major anti‐poverty measures in Portugal: the “Solidarity Supplement for the Elderly” (CSI) and the “Social Integration Income” (RSI). These two means‐tested measures were designed as the main components of the anti‐poverty social policy in Portugal, but they are directed at different groups of the population and have different objectives in terms of poverty reduction. Implemented since 1997, the aim of the RSI is to reduce extreme poverty through the reduction of poverty intensity of the most vulnerable sectors of the population. The CSI,gradually introduced since 2006, has the explicit objective of reducing the incidence of poverty on older people, its threshold defined at the level of the poverty line. Using a prototype of the Portuguese microsimulation model MicroSimPT , based on household micro‐data from the European Union Statistics on Income and Living Conditions (EU‐SILC), we simulate the impact of each measure and their joint effect on the income distribution and on different dimensions of monetary poverty. The size of government expenditure required to finance these programs will also be estimated.